REVIEW : PEMBUATAN NANOKOMPOSIT KARET ALAM / POLIOLEFIN / ORGANOBENTONIT - Ahmad Hafizullah Ritonga; Novesar Jamarun (JURNAL KIMIA SAINTEK DAN PENDIDIKAN, 2019)
Nanocomposites can be made by mixing three types of materials, namely natural rubber, polyolefin, and organobentonite. This article review discusses deproteinization of natural rubber using the incubation method, the grafting process of anhydrous maleate on natural rubber, either by reflux technique or by using an internal mixer, modification of natural rubber with thermoplastic materials in the form of polyolefins (such as polyethylene or polystyrene), and bentonite filler which is nanoparticle size and organic material has been modified to form organobentonite. The blending technique used in obtaining nanocomposites can be carried out either by the reflux method or the melting phase method using an internal mixer, while still using additive materials such as compatibility and initiator. The results showed that chemical bond occurred between natural rubber (NR) and polyolefins using NR-g-MA compatibility and peroxide initiator, and also the presence of nanofiller organobentonite that was spread evenly in the natural rubber / polyolefin material had improved the mechanical properties of the nanocomposite.